2016
DOI: 10.19082/2325
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the application of platelet rich plasma in sports medicine

Abstract: IntroductionIn recent years, platelet rich plasma (PRP) has been receiving increasing attention for the treatment of soft tissue injuries. These numerous applications have raised a great deal of questions and debate about the effectiveness of this method. This study aimed to determine the efficacy of PRP in improving sports injuries and subsequently throw some light on these controversies.MethodsA systematic review of the literature and meta-analysis of results were undertaken. All related databases, such as P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Although PRP shows some promise as a treatment for promoting faster healing in tendons, 20,50,51 the potential enhancement of healing demonstrated in laboratory studies is yet to be evidenced in the patient setting. The mechanisms of action through which PRP exerts its regenerative effects in humans are not completely understood.…”
Section: Achilles Tendon Injury and Platelet-rich Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Although PRP shows some promise as a treatment for promoting faster healing in tendons, 20,50,51 the potential enhancement of healing demonstrated in laboratory studies is yet to be evidenced in the patient setting. The mechanisms of action through which PRP exerts its regenerative effects in humans are not completely understood.…”
Section: Achilles Tendon Injury and Platelet-rich Plasmamentioning
confidence: 99%
“…52 An early systematic review of clinical trials of PRP in humans by Taylor et al 50 reported faster healing and better function in the management of tendon and ligament injuries. However, a more recent review by Gholami et al 51 reported no beneficial effects of PRP in the management of sports injuries for pain or function compared with other management options.…”
Section: Achilles Tendon Injury and Platelet-rich Plasmamentioning
confidence: 99%
“…Full texts were scrutinised against the inclusion and exclusion criteria, with a final inclusion of 29 SRs (Figure ) . Reasons for exclusion of studies at the second stage are presented by topic and clinical indication in Files …”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of explanations regarding the reasoning behind the conclusion can help the readers and affect the final conclusion. Age group of those studied as well as the duration of follow-up of effects should also be included in study evaluation [ 154 ].…”
Section: Discussionmentioning
confidence: 99%